2020
DOI: 10.1007/s00586-020-06499-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparable increases in dural sac area after three different posterior decompression techniques for lumbar spinal stenosis: radiological results from a randomized controlled trial in the NORDSTEN study

Abstract: Purpose To investigate changes in dural sac area after three different posterior decompression techniques in patients undergoing surgery for lumbar spinal stenosis. Summary of background data Decompression of the nerve roots is the main surgical treatment for lumbar spinal stenosis. The aim of this study was to radiologically investigate three commonly used posterior decompression techniques. Methods The present study reports data from one of two multicenter randomized trials included in the NORDSTEN study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…A secondary radiological study from this trial reported that UL, BL, and SPO provided a similar increase of the dural sac cross-sectional area (DSCA). 37 Hence, both radiological and clinical outcomes seem similar in the surgical techniques compared 2 years postoperatively. The outcome for these patients will be followed up with for 10 years to investigate eventual changes over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A secondary radiological study from this trial reported that UL, BL, and SPO provided a similar increase of the dural sac cross-sectional area (DSCA). 37 Hence, both radiological and clinical outcomes seem similar in the surgical techniques compared 2 years postoperatively. The outcome for these patients will be followed up with for 10 years to investigate eventual changes over time.…”
Section: Discussionmentioning
confidence: 99%
“…A decompressive procedure is performed to relieve the dural compression at the affected level of the spine and be comprehensive enough to achieve sufficient symptom relief. A secondary radiological study from this trial reported that UL, BL, and SPO provided a similar increase of the dural sac cross-sectional area (DSCA) . Hence, both radiological and clinical outcomes seem similar in the surgical techniques compared 2 years postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Unilateral laminotomy with bilateral decompression is considered to be the least invasive of the three procedures. No difference in clinical outcomes were found between the three techniques in prior work,16 and all three resulted in the same increase in DSCA 13. The trial protocol (supplement appendix 1) was approved by The Regional Committee for Medical and Health Research Ethics of Central Norway (REC Central), project identifier 2011/2034.…”
Section: Methodsmentioning
confidence: 99%
“…In the NORDSTEN Spinal Stenosis Trial (SST) it was found that three commonly used minimally invasive midline-retaining posterior decompression techniques resulted in a similar increase in DSCA. 13 In the present study, our sample is more than four times greater than those considered in previous studies, and our analyses focused specifically on the increase in DSCA following surgical decompression.…”
mentioning
confidence: 94%
“…over-the-top dekomprese nebo endoskopické techniky). Radiologická studie potvrdila stejnou efektivitu v dekompresi durálního vaku mezi jednostrannou laminotomií s druhostrannou šikmou dekompresí, oboustrannou laminotomií a laminektomií (23).…”
Section: Původní Práce Original Paperunclassified